Understanding the promotion of aerobic oxidation of benzyl alcohol over Pt-based catalysts - Kunene, Avela (Department of Chemical Engineering, 2022)
The combination of metal catalyst with molecular oxygen (which is the cheapest and the most environmental-friendly oxidant) is undoubtedly a more benign alternative to the existing methodologies for the oxidation of alcohol substrates to aldehydes, ketones and/or carboxylic acid products. However, a potential risk is apparent upon the use of volatile and flammable organic solvents, specifically in the presence of molecular oxygen. This makes the liquid-phase oxidation of alcohols a non-trivial chemical reaction that requires safety considerations. As such, designing a new alcohol oxidation procedure should carefully incorporate safety and sustainability principles while maintaining overall reaction efficiency. The solvent system should be considered carefully to limit potential risk associated with the oxidation of organic substrates using air/O2 as an oxidant at elevated temperatures. The use of H2O (as a non-flammable solvent) would not only present safety measure in alcohol oxidation (with O2 as an oxidant), but also has a potential to enhance overall catalytic performance. In this study the influence of H2O on the liquid phase benzyl alcohol oxidation is explored using a Pt/TiO2(P25). The rate of reaction at 90°C is significantly enhanced when using H2O as a solvent (TOF of 677.4 ± 23 hr-1 compared to the TOF obtained in solvent-free system, 27 ± 6 hr-1, in m-xylene as a solvent, 23 ± 2 hr-1, or in n-heptane as a solvent, 20 ± 2 hr-1). The promotional effect of H2O is associated with the mole fraction of H2O in the organic phase rather than fugacity of H2O in the system. It is thought that the precise role of H2O in the organic phase is thought to facilitate the H-transfer reactions. A DFT study suggests that the presence of H2O facilitates the dissociation of molecularly adsorbed O2 over Pt(111) surface resulting in the formation of surface hydroxyl species in addition to surface oxygen. The catalytic activity of platinum in the benzyl alcohol oxidation is suppressed significantly upon alloying Pt with Ni (forming Pt-skin Ni subsurface alloy). This is ascribed to a weakening of the chemical bond between Pt and adsorbed atomic oxygen due to the suppression of surface-states on the Pt surface layer, due to the presence of Ni atoms in the subsurface layer. In contrast to the effect associated with the presence of Ni in alcohol oxidation, the addition of Bi enhances the rate of the benzyl alcohol oxidation (but to a lesser extent the oxidation of the non-aromatic analogue, cyclohexyl methanol). The addition of bismuth results in the formation of Bi2Pt (together with some amorphous Bi2O3), which is partially oxidized upon exposure to oxygen. Bismuth is thought to be a sink for oxygen which may be involved in the selective oxidation of alcohols. The resulting surface hydroxyl groups are thought to be rapidly eliminated from the bismuth surface. Furthermore, bismuth is thought to induce electron backdonation in benzyl alcohol substrate, thus weakening the O-H bond of the alcohol; electron backdonation induced by Bi is improbable with cyclohexyl methanol as the substrate. Typically, the active metal, in heterogeneous catalysis immobilized on a metal oxide support. Platinum-based catalysts were synthesized by incipient wetness impregnation of TiO2(P25), CeO2, g-Fe2O3, g-Al2O3 and MoO3. The turnover frequency is strongly dependent on the type of support used indicating a strong involvement of the support on the benzyl alcohol oxidation. With the exception of Pt/g-Fe2O3, it is apparent that the reducibility of the oxide support together with the ability to form OH on the oxide plays an important role. It is thought that the alcohol substrate may interact with oxygen on the support, which may result in the formation of a surface hydroxyl species on the reducible support, which can be eliminated generating an oxygen vacancy on the oxide. This ultimately improves the overall TOF for benzyl alcohol oxidation. Hence, support materials which can generate surface hydroxyl groups, and eliminate them under reaction conditions in the form of water, will be enhance the benzyl alcohol oxidation.